Effect of 30 Minutes Walking on Decreasing Blood Sugar Levels in Diabetes Mellitus Patients Type 2 in Kwala Mencirim Village - Masdalifa Pasaribu (Universitas Islam Negeri Sumatera Utara, Medan, 2021)
Diabetes Mellitus is a global problem that occurs at this time Diabetes Mellitus sufferers are at risk of experiencing various complications if not properly controlled and can cause death. This study aimed to determine the effect of walking for 30 minutes on reducing blood sugar levels in Type 2 Diabetes Mellitus patients in Kwala Mencirim Village. This research is a type of quantitative research using a Quasi-experimental research design, with the One Group Pre-post Test Design research design. The research was conducted in Kwala Mencirim Village, Langkat Regency, North Sumatra Province. The time of this research was in May-August 2021. The population of this study were all Type 2 Diabetes Mellitus sufferers in Kwala Mencirim Village, totaling 80. The research sample was 10 patients with Type 2 Diabetes Mellitus. The sampling technique used Purposive Sampling. Data collection was carried out using observation sheets, blood sugar digital devices. Data analysis was performed by paired t-test with Wilcoxon. The results showed an effect of walking 30 minutes on reducing blood sugar levels in patients with Type 2 diabetes mellitus (p=0.001 <α 0.05) in Kwala Mencirim Village, Langkat Regency, North Sumatra Province. With an average pretest blood sugar level of 220 mg/dl and a post-test of 212 mg/dl. It is recommended for Health Workers to be able to apply 30 minutes of walking therapy to reduce or stabilize Blood Sugar Levels in Type 2 Diabetes Mellitus patients and it is suggested to the public, especially people with Diabetes Mellitus, to more routinely do 30 minutes of walking therapy without drugs.Keyword: Blood Sugar Levels, Type 2 Diabetes Patients, Walking